Specific and non-specific suppression of renal allograft rejection in the rat - Winearls, C; Winearls, Christopher Good (1978)
In this thesis certain clinically relevant aspects of specific and non-specific suppression of renal allograft rejection were examined in a rat renal allograft model. The potentiation of the partial immunosuppressive effect of passive enhancement was found to be possible with suboptimal doses of antilymphocyte serum or cyclophosphamide but not azathioprine and prednisolone. Moreover, the use of high doses of azathioprine with enhancing serum resulted in significantly shorter survival times than those seen with enhancing serum alone. It was concluded that potentiation of enhancement required a significant but suboptimal level of non-specific immunosuppression with the appropriate agent to be applied during the induction of enhancement. The administration of antidonor antiserum to rat kidney allograft recipients does not usually result in damage to the graft but it is likely to occur in human allograft recipients. The enhancing capacity of the noncomplement- fixing, F(ab')2 fraction of enhancing antibody was investigated and found to be 100 x less effective than whole antibody in the induction of enhancement. However, F(ab')2 was found to be capable of blocking antibody-mediated damage to allografts caused by whole antibody and guinea-pig complement, without blocking the latter's specific immunosuppressive effect. Red cell absorption of enhancing serum to produce a putative, "anti-Ia-like" serum, resulted in the loss of the serum's ability to produce immediate antibody-mediated damage to a renal allograft without removing its ability to enhance. Both strategies could, with appropriate modifications, be applied to clinical practice. Antilymphocyte serum and cyclophosphamide, which were thought to have relatively selective actions on cellular and humoral immunity respectively, were found to have no such selectivity in the suppression of renal allograft rejection. When used in combination their effects were found to be additive but not synergistic.